How to Characterize Soil Variability in Florida Citrus Groves as It Relates to Tree Growth and Yield - Kirandeep K. Mann; Arnold W. Schumann; Thomas A. Obreza; Willie G. Harris; Jerry B. Sartain (EDIS, 2012)
Non-uniform tree growth and fruit yield are very common throughout many Florida citrus groves, but variable groves are typically managed as if they were uniform. This 4-page fact sheet provides information about the relationship between soil variability and citrus production, proposes recommendations for soil sampling that account for spatial variability, and suggests site-specific management practices for variable Florida citrus groves. Written by Kirandeep K. Mann, Arnold W. Schumann, Thomas A. Obreza, Willie G. Harris, and Jerry B. Sartain, and published by the UF Department of Soil and Water Science, January 2012.